SENTRA GALERI KERAJINAN TENUN KALIMANTAN BARAT DI KOTA PONTIANAK - Eriyanty, Elen; Affrilyno, Affrilyno; Caesariadi, Tri Wibowo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2020)
Local residents of West Borneo have expertise in producing variety of traditional crafts, one of which is woven fabrics, which is no less competitive with other regions. But there are several problems regarding the lack of facilities and infrastructure, such as less productive weaving processes, exhibitions that are held irregularly, difficulty of marketing products and no place for discussion. Therefore, the need of a place to product, exhibit, and market the products of West Borneo woven fabrics called